Vai-vem mareta: notas sobre ciências do rio Peruaçu - Isabela Oliveira Izidoro (2022)
In a scenario of climate collapse, mass extinctions, and the increasing of historical violence against territories, people, animals and plants of the countryside, forest and water, this study seeks to learn the sciences of environments in the company of the beings that inhabit them. Along the Peruaçu River, a tributary of the São Francisco, in northern Minas Gerais, Brasil, and despite the impossibility of being in the field for most of the research due to the Covid-19 pandemic, I’ve worked in two ways: listening to, transcribing and editing classes, workshops, and other verbal communications as an important tool for studying and theoretical deepening; and shared research with interlocutors from the Peruaçu Valley, with whom I devise experiments, among them the game Temporão, shared in March 2022 with schools in the region, and walks around the watershed in March, July and August 2022. The writing is structured through walks accompanied by river-beings, based on the multispecies alliances that make possible different ways of creating worlds in Peruaçu, intending to generate a polyphonic text as a way to circulate the research in the territory where it takes place. Throughout the master’s degree, it becomes evident that the sciences of the Peruaçu River are not only in its ravines, banks, and riverbed; but also in the kitchens, cisterns, filters, gardens, and wherever else women are in their daily work with the land, the plants, the waters, and the family and neighborhood’s health.